Risk of RSV-related hospitalization is associated with gestational age in preterm (born at 29-34 wGA) infants without outpatient palivizumab administration - Elizabeth R. Packnett; Isabelle H. Winer; Abiola Oladapo; Matthew Wojdyla (Taylor & Francis Group, 2023)
Palivizumab has been shown to decrease RSV-related hospitalization (RSVH) risk and reduce RSVH severity. American Academy of Pediatrics (AAP) guidance on administration of palivizumab has changed over time; in 2014, palivizumab was no longer recommended in preterm infants born at 29 weeks gestational age (wGA) or later. This study's objective was to describe RSVH risk and severity in preterm infants (29-34 wGA) without comorbidities relative to healthy term infants and to each other by gestational age. Using the MarketScan Multi-State Medicaid and Commercial Databases, infants born from July 1, 2014 to June 30, 2019, at 29-34 wGA (preterm) and >37 wGA (term) were identified. During RSV seasons (November to March) from 2014 to 2020, claims incurred by infants while they were <6 months old were evaluated for RSVH and RSVH characteristics. This study included 63,351 preterm infants and 1,076,389 term infants without outpatient palivizumab administration. Rate of RSVH was higher in infants with lower wGA at birth and ranged 3.32-5.72 per 100 infant-seasons in Medicaid-insured infants and 3.21-4.84 in commercially insured infants. Relative risk of RSVH was 5-8 times higher in Medicaid-insured preterm infants and 3-5 times higher in commercially insured preterm infants compared to term infants. ICU admissions and mechanical ventilation were more common during RSVH in preterm infants relative to term infants. RSV-related outpatient healthcare utilization was also 2-3 times higher in preterm infants born at 31-34 wGA. Increased utilization of palivizumab among infants born at 29-34 wGA may decrease RSVH rates and result in less severe course in preterm infants with RSVH.